Irradiation Nation [food safety]. - Goldstein, H. (IEEE spectrum)
Electron beams and X-rays might make some foods safer to eat. But is irradiation a silver bullet or an industrial-strength placebo for killer contaminants in the food chain? This paper discusses the technology and issues involved in this aspect of food safety. Even though it is highly effective at killing bugs and bacteria, irradiation is at best only a partial solution to the problem of food safety.